2022
DOI: 10.1002/art.42104
|View full text |Cite
|
Sign up to set email alerts
|

Role for Granulocyte Colony‐Stimulating Factor in Neutrophilic Extramedullary Myelopoiesis in a Murine Model of Systemic Juvenile Idiopathic Arthritis

Abstract: Objective Systemic juvenile idiopathic arthritis (JIA) is a systemic inflammatory disease with childhood onset. Systemic JIA is associated with neutrophilia, including immature granulocytes, potentially driven by the growth factor granulocyte‐colony stimulating factor (G‐CSF). This study was undertaken to investigate the role of G‐CSF in the pathology of systemic JIA. Methods Injection of Freund's complete adjuvant (CFA) in BALB/c mice induces mild inflammation and neutrophilia in wild‐type (WT) mice and a mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Characterization of neutrophils using surface markers and single-cell RNA sequencing revealed that G-CSF induced immature neutrophils and myeloid derived suppressor-like cells. Intriguingly, manifestations such as extramedullary myelopoiesis and arthritis were ameliorated by G-CSF blockade but weight loss and elevation of plasma cytokine levels such as IL-6, IL-17, and TNF-α were worsened [ 69 ]. Overall, G-CSF and neutrophils appear to play both pathogenic and protective roles in this model.…”
Section: Animal Models For Mas and Sjiamentioning
confidence: 99%
“…Characterization of neutrophils using surface markers and single-cell RNA sequencing revealed that G-CSF induced immature neutrophils and myeloid derived suppressor-like cells. Intriguingly, manifestations such as extramedullary myelopoiesis and arthritis were ameliorated by G-CSF blockade but weight loss and elevation of plasma cytokine levels such as IL-6, IL-17, and TNF-α were worsened [ 69 ]. Overall, G-CSF and neutrophils appear to play both pathogenic and protective roles in this model.…”
Section: Animal Models For Mas and Sjiamentioning
confidence: 99%
“…Animal studies have clearly demonstrated that enhanced myelopoiesis and activation of HSPCs is a characteristic of experimental arthritis. 58 , 59 Similarly, myeloid skewing of HSPCs has been observed in patients and mice with systemic lupus erythematosus (SLE). 60 Finally, bone marrow inflammation has been found in patients with periodontitis, a disorder that is also associated with cardiometabolic risk.…”
Section: Rewiring Of Hspc In Cardiometabolic Disordersmentioning
confidence: 94%
“…The adoptively transferred MDSCs exacerbated the disease and expanded the differentiation of Th17 cells in an IL-1β-dependent manner [79]. G-CSF-induced extramedullary myelopoiesis was shown critical for the expansion of PMN-MDSCs in juvenile idiopathic arthritis, as its blockage in CFA-immunized IFN-γ KO mice, could ameliorate the arthritis [80]. In other studies, a significant increase in circulating MDSCs in RA patients and plasma Arg-1 levels inversely correlated with the frequency of Th17 cells, suggesting their beneficial role in RA [81].…”
Section: Multiple Sclerosis (Ms) Is Characterized By Overactivated My...mentioning
confidence: 99%